Evaluation of Health Status and Factors Associated with Health Behaviors among Adults in Saudi Arabia - Alsadoun, Ahmed (Asian Journal of Pharmaceutics (AJP), 2024)
Background and Objectives: Despite the available treatment options, people’s attitudes toward health change significantly. Evaluation of health status, and factors associated with health behaviors among adults in Saudi Arabia. Materials and Methods: A cross-sectional web-based study was conducted in early, 2021 using a valid, self-administered online questionnaire, the data was analyzed using Statistical Package for Social Science version 26. Results: Among the respondents a greater proportion of them were males 68.8% (n = 574), slightly more than half 54.6% (n = 456) were consulted physicians, while 19.4% of them (n = 192) visited pharmacists for seeking health care, 16.4% (n = 137) used herbal or alternative medicine. A greater percentage of women seek physicians (56.9%) in comparison to men (53.5%), while more men prefer to consult pharmacists (20%) in comparison to females (18.1%), also women used more herbal medicine for seeking treatment in comparison to men. The health-seeking behavior is significantly associated with being a female gender (P = 0.0001), nationality of the participant (P = 0.0001, employment (P = 0.0001), and age of the individual (P = 0.0001). Conclusion: Increasing public understanding of the rational choice of seeking health care is a critical issue in maintaining an individual’s health.